Magnitude or direction? Seasonal variation of inter-limb asymmetries in elite academy soccer players - Bishop, C.; Read, P.; Chavda, S.; Turner, A. (The Journal of Strength and Conditioning Research, 2021)
Purpose: Inter-limb asymmetry has been a popular line of investigation in recent years; however, previous research has highlighted that a distinct lack of longitudinal data exists on the topic. Therefore, the aims of the present study were to provide seasonal variation data for the magnitude and direction of asymmetry. Methods: Eighteen elite male academy soccer players (under-23) performed unilateral countermovement jumps (CMJ) and unilateral drop jumps (DJ) during pre, mid and end of season time points. Recorded metrics for jump tests and asymmetry included: jump height, peak force and concentric impulse for the CMJ, and jump height, ground contact time and reactive strength index for the DJ. For statistical analysis, absolute (CV) and relative (ICC with 95% confidence intervals) reliability were presented at each time point. Friedman's ANOVA was conducted to determine systematic bias between time points for asymmetry, with statistical significance set at p < 0.05. Magnitude of change was also determined using Cohen's d effect sizes and interpreted based off the scale: < 0.2 = trivial, 0.2-0.6 = small, 0.61-1.2 = moderate and 1.21-2.0 = large. Kappa coefficients were calculated to determine levels of agreement for how consistently asymmetry favoured the same leg. This method was chosen because it describes the portion of agreement between 2 methods after any agreement by chance has been removed and values were interpreted as follows: < 0 = poor, 0.01-0.20 = slight, 0.21-0.40 = fair, 0.41-0.60 = moderate, 0.61-0.80 = substantial and 0.81-0.99 = nearly perfect. Results: The magnitude of asymmetry showed no significant changes throughout the season for any metric in either test. This was supported through effect size data which showed trivial to small changes throughout the season (CMJ effect size range = -0.60 to 0.55; DJ effect size range = -0.19 to 0.41). However, Kappa coefficients showed poor to substantial levels of agreement for the direction of asymmetry during the CMJ (Kappa = -0.06 to 0.77) and DJ (Kappa = -0.10 to 0.78) throughout the season. Conclusions: These data show that when monitoring asymmetry, the magnitude alone provides a false impression of consistent scores over time (as represented by trivial to small changes). However, this notion seems strange given numerous empirical studies have shown the task-specific nature of asymmetry and its highly variable nature. In contrast, monitoring the direction of asymmetry highlights the inherent within-group variability (as represented by the varying levels of agreement between time points), and is suggested as a useful tool for practitioners who wish to monitor asymmetry over the course of a competitive soccer season. Practical Application: These data show the importance of investigating both component parts of asymmetry (i.e., addressing both limbs, given that it is a ratio statistic). Thus, monitoring the direction of asymmetry enables practitioners to determine whether existing inter-limb differences are consistent between time points or whether changes in limb dominance are evident. If and when the latter presents itself, this may highlight fluctuations in natural performance variability, rather than a consistent asymmetry which always favours the same limb.